ADAM17-Mediated Reduction in CD14++CD16+ Monocytes ex vivo and Reduction in Intermediate Monocytes With Immune Paresis in Acute Pancreatitis and Acute Alcoholic Hepatitis - Waller, Kathryn; James, Charlotte; de Jong, Anja; Blackmore, Laura; Ma, Yun; Stagg, Andrew; Kelsell, David; O'Dwyer, Michael; Hutchins, Robert; Alazawi, William (Frontiers in Immunology, 2019)
Impaired immune responses and increased susceptibility to infection characterize acute inflammatory conditions such as pancreatitis and alcoholic hepatitis and are major causes of morbidity and mortality. However, the mechanisms that drive this apparent immune paresis remain poorly understood. Monocytes mediate host responses to damage and pathogens in health and disease, and three subsets of monocytes have been defined based on CD14 and CD16 expression. We sought to determine the changes in monocyte subsets in acute pancreatitis (AP) and acute alcoholic hepatitis (AAH), together with functional consequences and mechanisms that underlie this change. Peripheral blood mononuclear cells (PBMCs) from patients with AP or AAH were compared with healthy controls. Monocyte subsets were defined by HLA-DR, CD14 and CD16 expression. Changes in surface and intracellular protein expression and phosphorylation were determined by flow cytometry. Phenotype and function were assessed following stimulation with lipopolysaccharide (LPS) or other agonists in the presence of specific inhibitors of TNFα and a disintegrin and metalloproteinase 17 (ADAM17). Patients with AP and AAH had reduced CD14++CD16+ intermediate monocytes compared to controls. Reduction of intermediate monocytes was recapitulated ex vivo by stimulating healthy control PBMCs with Toll-like receptor (TLR) agonists LPS, flagellin or polyinosilic:polycytidylic acid (poly I:C). Stimulation caused shedding of CD14 and CD16, which could be reversed using the ADAM17 inhibitor, TMI005 but not direct inhibitors of TNFα, a known ADAM17-target. Culturing PBMCs from healthy controls resulted in expansion of intermediate monocytes, which did not occur when LPS was in the culture medium. Cultured intermediate monocytes showed reduced expression of CX3CR1, CCR2, TLR4 and TLR5. We found reduced migratory responses, intracellular signaling and pro-inflammatory cytokine production, and increased expression of IL-10. Stimulation with TLR agonists results in ADAM17-mediated shedding of phenotypic markers from CD16+ monocytes, leading to apparent ‘loss’ of intermediate monocytes. Reduction in CD14++CD16- monocytes and increased CD14++CD16+ is associated with altered responses in functional assays ex vivo. Patients with AP and AAH had reduced proportions of CD14++CD16+ monocytes and reduced phosphorylation of NFκB and IL-6 production in response to bacterial LPS. Together, these processes may contribute to the susceptibility to infection observed in AP and AAH.